The critical discourse on the novel Twilight of Karaki Saad Mohammed Rahim - Ahmed, Fahim Tumaa (Al-Adab Journal, 2022)
An Arabic novel In Iraq has been anotable Progress in its modern buildings and technical, by a number of narrative Culture and bright names which had its echo and Sound at that time. We mantion The great Iraqi Novelist saad Mohammed Raheem who began his Literary Career Tells Several books and narrative groups Then he began writing novels after its best Technologises, Passion and Classif ancy- He Wrote Many novels like his Famous (Gassak Al- Karak) there on The novel (Tarneema Imraa Shafak al- Bahar), The novel (Maktal Baia al- Kutub) and etc.Our Facus was on the novel (Gassak Al- Karak) which was the most Important one was Published in 2000 and won the First a word in novel Competition in Iraq. Wle we Searched the tercultural of Critical discourse around the novel (Gassak Al- Karak) we will Cover the Most Important Studies and Critical articales which Surounded This novel ane it Made to analysis an Important and technical Litrary anylasis.It was as Important as it was Over many novel at that Time. These articles and Cash newspapers were Focused on Important Side in The novel e specially in its shape, Structural and narrative elements. Critics Stood at the litle threshold be Cause it represonted the First Station From the novels Stations, Surounded to hero Character in Writing novels and giving an idea of it From the other Side, Study the Search Technologies, The Modern novels and after modren especially the obgect of Intertextual, Fragmented and College Because the Considered Important Elements and techocal in Building novels and one Reason for its Success From other Modren novels in Iraq.